SIKAP PETANI TERHADAP USAHA PEMBIBITAN DURIAN DI KECAMATAN KEMRANJEN KABUPATEN BANYUMAS - HERMANTO HUTABARAT (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2013)
Subdistrict Kemranjen Banyumas known as a center for the development of durian and durian seedlings Farmers in the District Kemranjen buy durian seedlings in Salatiga before seeking his own nursery. As a result of the lack of capital because of high transport costs, the farmers developed a durian seedlings. The entry of breeding leads to changes in the business. Durian seedlings have attributes that make farmers prefer the nursery business. The purpose of this study was to determine the attitude of farmers towards breeding durian, knowing the components forming the attitude and the attitude of farmers towards the attributes contained in durian seedlings. The method used was a survey method. Header retrieval techniques using simple random sampling. The samples used were 67 respondents. Results of the study is the total score obtained by all farmers is 10379, located in the field between the third quartile and maximum attitude Based on the criteria, it can be concluded that farmers strongly agreed or strongly positive for breeding durian . Farmers have a good attitude towards the attributes of durian seed is indicated by the value in the category 109.3228 (interpretation) is positive. Attitude strongly agree or strongly positf forming attitudes of farmers towards variable, namely: availability of capital (35.8 % of the farmers responded to agree), the availability of experts (66 % of farmers responded to agree), the skills of farmers (48.5 % of the farmers responded to agree), the selling price products (54.1 % of farmers responded strongly agree), the price of the means of production (72 % of farmers responded strongly agree), the availability of means of production (81.3 % of farmers responded strongly agree ), the total cost of production (50.4 % of the farmers responded agree), earned income (51.5 % of farmers responded strongly agree) and the benefits to be obtained (60.8 % of the farmers responded to agree). Keyword: Attitute, effort and durian.